ANALISIS PENGUKURAN PRODUKTIFITAS KEUANGAN MENGGUNAKAN METODE VALUE ADDED PADA HOTEL PEONY PONTIANAK - Dhidik Apriyanto (Jurnal Administrasi Bisnis, 2013)
Increasing productivity is a definite price that a company must pay to maintain its existence. As a point of entrance, Pontianak is visited by visitors coming to Kalimantan Barat by sea or air transportation. Therefore, hotel business flourishes in line with the development of tourism in Kalimantan Barat which owns cultural variety with its Dayak, Malay, and Tiongha tribes. One of the hotels is Hotel Peony. This study is aimed to find out the financial performance of Hotel Peony Pontianak by using Value Added which is deemed suitable to measure financial performance of a company. Value Added cosists of three main unit analyses: the unit profit, the unit depreciation cost, and the unit labor cost. This study yields a number or recommendations to improve financial productivity in Hotel Peony. The hotel needs to be selective in its expenses, recruit more employees, and increase employees’ income to motivate employees in improving their performance.